ANALYSIS OF FINANCIAL DISTRESS IN INDONESIA STATE-OWNED ENTERPRISE - Didik Prasetyanto; Agung Nur Probohudono; Nur Chayati; Saktiana Rizki Endiramurti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to provide empirical evidence related to the potential for financial distress experienced by State-Owned Enterprises. Through this research, a description of the potential financial distress experienced by PT Wijaya Karya (Persero) Tbk and PT Adhi Karya (Persero) Tbk can be obtained during the period 2010 - 2019. The Financial distress prediction model uses the Altman Model (Z-Score) and Springate Model (S-Score). The results show that from 2010 – 2019, PT Wijaya Karya (Persero) Tbk is still in a healthy condition so that the possibility of going bankrupt is very small. However, year by year, the condition of PT Wijaya Karya (Persero) Tbk is still in a gray condition where in this condition the company is prone to bankruptcy and experiencing financial problems that must be handled by the company's management appropriately. Meanwhile, PT Adhi Karya (Persero) from 2010 – 2019 showed the potential for financial distress which was strengthened by an unhealthy balance sheet because most of the funding sources came from debt. This study shows that the potential for financial distress arises because of a shift in government policy in development.